2021
DOI: 10.1038/s41467-020-20569-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a new Leishmania major strain for use in a controlled human infection model

Abstract: Leishmaniasis is widely regarded as a vaccine-preventable disease, but the costs required to reach pivotal Phase 3 studies and uncertainty about which candidate vaccines should be progressed into human studies significantly limits progress in vaccine development for this neglected tropical disease. Controlled human infection models (CHIMs) provide a pathway for accelerating vaccine development and to more fully understand disease pathogenesis and correlates of protection. Here, we describe the isolation, chara… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 82 publications
(85 reference statements)
1
23
0
Order By: Relevance
“…In conclusion, the successful completion of this study complements further research aimed at developing a CHIM model for leishmaniasis. As reported elsewhere 84 , using a new fully characterised strain of Leishmania major, we have manufactured a clinical parasite bank under GMP conditions and confirmed that this isolate is fully transmissible to rodents via the bite of either P. papatasi and P. dubosqi. How well these preclinical and clinical studies translate into an effective CHIM will be addressed in a subsequent clinical study (LEISH_Challenge; ClinicalTrials.gov ID NCT04512742).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In conclusion, the successful completion of this study complements further research aimed at developing a CHIM model for leishmaniasis. As reported elsewhere 84 , using a new fully characterised strain of Leishmania major, we have manufactured a clinical parasite bank under GMP conditions and confirmed that this isolate is fully transmissible to rodents via the bite of either P. papatasi and P. dubosqi. How well these preclinical and clinical studies translate into an effective CHIM will be addressed in a subsequent clinical study (LEISH_Challenge; ClinicalTrials.gov ID NCT04512742).…”
Section: Discussionsupporting
confidence: 79%
“…First, it is known that sand fly behaviour is altered following infection with Leishmania parasites, although usually this is associated with increased bite rate 96 . Though previous studies on mice revealed that L. major-infected females of both species readily take a bloodmeal on mice 84 , and P. duboscqi infected with L. major can cause cutaneous leishmaniasis in mice 97 and non-human primates 98 , we cannot be certain that the biting characteristics on human subjects will be faithfully reproduced using infected sand flies in a CHIM study. The second issue relates to uniformity between participants, which may impact on outcomes from a future CHIM.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…One approach may be to consider a controlled human infection model (CHIM) that could provide a pathway for accelerated vaccine development and to identify correlates of protection. Recently, L. major strains have been developed under GMP conditions and characterized for potential use in CHIM studies that can be used in CL vaccine trials (Ashwin et al, 2021). CHIM trials would not however be possible for VL due to the risk from challenge infections with a visceral disease causing Leishmania species such as L. donovani.…”
Section: Alternative Methods For Determining the Efficacy Of A Leishmania Vaccinementioning
confidence: 99%
“…Currently, only one therapeutic clinical trial is ongoing (Clinicaltrials.gov NCT03969134), and a clinical-grade genetically attenuated live L. major vaccine is due to be manufactured in 2021 [20] to support future trials. Recent progress towards the development of a controlled human challenge model for CL [21,22] may also provide a stimulus for the clinical development of other candidate vaccines. However, the absence of a consensus on the size of the target populations, the paucity of data to support an indication for use in each disease state and the lack of realistic demand scenarios are likely determinants of the scarce interest from the pharmaceutical industry and philanthropic donors.…”
Section: Introductionmentioning
confidence: 99%